Effectiveness of Yijinjing exercise in the treatment of early-stage knee osteoarthritis: a randomized controlled trial protocol - Yihang Wang; Fei Yao; Min Fang; Guangxin Guo; Xiruo Xu; Kaiqiu Lu; Xuanying Zhu; Yijia Gu; Guangpu Yang (BMJ Open)
Introduction Knee osteoarthritis (KOA) is still a challenging degenerative joint disease with high morbidity and disease burden. Early-stage KOA, the focus of this study, could present a Window of Opportunity to arrest the disease process and reduce the disease burden. Yijinjing exercise is an important part of physical and psychological therapies in Traditional Chinese Exercise and may be an effective treatment. However, there is no clinical efficacy assessment of Yijinjing exercise for patients with early-stage KOA. Therefore, we designed a randomised controlled trial to evaluate the effectiveness of Yijinjing exercise on patients with early-stage KOA.Methods and analysis This is a parallel-design, two-arm, analyst assessor-blinded, randomised controlled trial. In total, 60 patients with early-stage KOA will be recruited and randomly assigned to the Yijinjing exercise group (n=30) and health education group (n=30) at a ratio of 1:1, receiving 12 weeks of Yijinjing exercise or health education accordingly. The primary outcome will be measured with the Western Ontario and McMaster Universities Osteoarthritis Index, and the secondary outcomes will include the Visual Analogue Scale, Short-Form 36 Item Health Survey Questionnaire, Beck Depression Inventory, Perceived Stress Scale, Berg Balance Scale, and Gait Analysis for a comprehensive assessment. Outcome measures are collected at baseline, at 12 week ending intervention and at the 12 week, 24 week and 48 week ending follow-up. The primay time point will be 12 weeks postintervention. Adverse events will be recorded for safety assessment.Ethics and dissemination This study has been approved by the ethical application of the Shanghai Municipal Hospital of Traditional Chinese Medicine Ethics Committee (2021SHL-KY-78).Trial registration number ChiCTR2200065178